The what and how of Family business paradox: Literature-inspired distillations and directions. (May 2020) - Barrett, Mary A; Moores, Ken
The purpose of this article is to review and comment on the literature on family business paradox against the backdrop of Moores and Barrett's 4Ls learning framework. This framework outlined the learning paradoxes, priorities and pathways that successful family business CEOs identified and coped with in their learning journeys. A 'what and how' theme emerges from our literature review (203 items) where we identify both confirmations and deficiencies in the 4Ls framework – deficiencies that suggest future research opportunities. Research directions are distilled in the form of questions that extend the 4Ls by enhancing the model both within it and by connecting it with adjacent areas.